Case report: A novel CACNA1S mutation associated with hypokalemic periodic paralysis - Nuzhnyi, Evgenii P.; Arestova, Alina S.; Rossokhin, Alexey V.; Protopopova, Anna O.; Abramycheva, Nataliya Yu; Suponeva, Natalia A.; Illarioshkin, Sergey N. (Frontiers in Neurology, 2023)
Background Hypokalemic periodic paralysis (HypoKPP) is a rare neuromuscular genetic disorder causing recurrent episodes of flaccid paralysis. Most cases are associated with CACNA1S mutation, causing defect of calcium channel and subsequent impairment of muscle functions. Due to defined management approaches early diagnosis is crucial for promptly treatment and prevention new attacks. Materials and methods We report a case of HypoKPP associated with previously unreported mutation in CACNA1S gene (p.R900M). Molecular modeling of CaV1.1 was applied to evaluate its pathogenicity. Results As a patient referred between attacks neurological status, laboratory and neurophysiological examination were unremarkable. Molecular modeling predicted that the p.R900M mutation affects the process of calcium channels activation. Conclusion Novel CACNA1S mutation, associated with HypoKPP was identified. Monte-Carlo energy minimization of the CaV1.1 model supported the association of this mutation with this disease.